The Mycobacterium tuberculosis Rv2745c plays an important role in responding to redox stress. - Amanda McGillivray; Nadia Abrahams Golden; Uma Shankar Gautam; Smriti Mehra; Deepak Kaushal (PLoS ONE)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), is the leading cause of death from an infectious disease worldwide. Over the course of its life cycle in vivo, Mtb is exposed to a plethora of environmental stress conditions. Temporal regulation of genes involved in sensing and responding to such conditions is therefore crucial for Mtb to establish an infection. The Rv2745c (clgR) gene encodes a Clp protease gene regulator that is induced in response to a variety of stress conditions and potentially plays a role in Mtb pathogenesis. Our isogenic mutant, Mtb:ΔRv2745c, is significantly more sensitive to in vitro redox stress generated by diamide, relative to wild-type Mtb as well as to a complemented strain. Together with the fact that the expression of Rv2745c is strongly induced in response to redox stress, these results strongly implicate a role for ClgR in the management of intraphagosomal redox stress. Additionally, we observed that redox stress led to the dysregulation of the expression of the σH/σE regulon in the isogenic mutant, Mtb:ΔRv2745c. Furthermore, induction of clgR in Mtb and Mtb:ΔRv2745c (comp) did not lead to Clp protease induction, indicating that clgR has additional functions that need to be elucidated. Our data, when taken together with that obtained by other groups, indicates that ClgR plays diverse roles in multiple regulatory networks in response to different stress conditions. In addition to redox stress, the expression of Rv2745c correlates with the expression of genes involved in sulfate assimilation as well as in response to hypoxia and reaeration. Clearly, the Mtb Rv2745c-encoded ClgR performs different functions during stress response and is important for the pathogenicity of Mtb in-vivo, regardless of its induction of the Clp proteolytic pathway.